Talent Management in Human Resource Management to Improve Organizational Performance - Jung Sen; Adi Harianto; Ika Puspa Satrianny (PT FORMOSA CENDEKIA GLOBAL, 2023)
Adaptation companies to pass talent management need at global era in view of information current and fast change and then continuous.Human resources with new talent for organization is need to achieve organization success/performance. Organization must time increase and energy to repair performance from new talent. Talent will compete do the best for organization when organization will appreciate the job. The findings from this study are talent management practices with a strong focus on business strategy and its alignment with overall business goals. These practices have statistically highly significant impact on corporate profits; one that is greater than that of any other focus of talent management practices. This research paper suggested that the management and individuals need to establish metrics and communicate the impact of the organization’s talent management efforts